2009
DOI: 10.1002/app.31042
|View full text |Cite
|
Sign up to set email alerts
|

In vitro release kinetics of bovine serum albumin from highly swellable dextran hydrogels

Abstract: Hydrogels synthesized from a polysaccharide-based polymer, dextran, in the presence of two crosslinking agents, N,N 0 -methylenebisacrylamide and epichlorohydrin, were evaluated for the oral colon-specific delivery of polypeptide drugs. These novel dextran hydrogels had significantly greater swelling ratios than recently developed dextran hydrogels. A model protein, bovine serum albumin, was loaded into 50% (by weight) crosslinker-containing dextran hydrogels in two ways: during the crosslinking reaction and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Also, the short half-life of protein drugs and their limited transit time in the gastrointestinal tract represent major challenges (El-Sherbiny, Abdel-Bary, & Harding, 2010;Ramadas, Paul, Dileep, Anitha, & Sharma, 2000). To date, several trials have been reported to overcome these shortcomings and to formulate peptide and protein drugs with maximum oral bioavailability (Dolatabadi-Farahani, Vasheghani-Farahani, & Mirzadeh, 2006;El-Sherbiny et al, 2010;Heller et al, 2002;Imren, Gumusderelioglu, & Guner, 2010;Liu, Jiao, & Zhang, 2007;Mi et al, 2005;Rekha & Sharma, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Also, the short half-life of protein drugs and their limited transit time in the gastrointestinal tract represent major challenges (El-Sherbiny, Abdel-Bary, & Harding, 2010;Ramadas, Paul, Dileep, Anitha, & Sharma, 2000). To date, several trials have been reported to overcome these shortcomings and to formulate peptide and protein drugs with maximum oral bioavailability (Dolatabadi-Farahani, Vasheghani-Farahani, & Mirzadeh, 2006;El-Sherbiny et al, 2010;Heller et al, 2002;Imren, Gumusderelioglu, & Guner, 2010;Liu, Jiao, & Zhang, 2007;Mi et al, 2005;Rekha & Sharma, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…For example, the dextran hydrogel crosslinked by epichlorohydrin, phosphorus oxychloride, and N,N ′ ‐methylenebisacrylamide is only suitable for protein postloading method, because the epoxy group of epichlorohydrin is also able to react with the amine or hydroxyl groups of protein, which can change the protein chemistry structure and lead to a unpredictable release dynamics . A postloading method can also lead to nonhomogeneous and nonuniform drug distribution within the hydrogel matrix as most of the postloaded drugs stay near the surface of the hydrogels.…”
Section: Resultsmentioning
confidence: 99%
“…The work presented is a contribution along these lines based on newly designed PAAm/dextran gels. The properties of dextran gels were examined recently by Imren et al seeking highly swellable hydrogels 16. However, in our case, the best gels must have the opposite property in order to preserve as much as possible their original size in various media used in proteomics for staining gels.…”
Section: Introductionmentioning
confidence: 87%